Electroactivity of NiCr Catalysts for Urea Oxidation in Alkaline Electrolyte. Issue 17 (26th July 2017) - Singh, Ramesh Kumar; Schechter, Alex
Abstract: Inexpensive Ni‐based catalysts have shown comparable urea oxidation activity to that of precious metals in an alkaline electrolyte. We investigated the urea oxidation on binary NiCr catalysts supported on a carbon matrix in 1 m KOH and 0.33 m urea. The amount of Cr was optimized in the catalyst layer, and it was found that the catalyst with 40 % Cr (Ni60 Cr40 /C) exhibits the highest urea oxidation activity of 2933 mA mgNi −1 at 0.55 V; with an onset potential of 0.32 V vs. Ag/AgCl. Chronoamperometry curves of NiCr catalysts show stability over 2000 s in oxidizing urea. A lower charge‐transfer resistance of 3.3 Ω cm 2 at 0.40 V was calculated on Ni60 Cr40 /C compared to that on Ni/C (13 Ω cm 2 ). The exceptionally high mass activity of Ni60 Cr40 /C is attributed to its improved charge‐transfer kinetics, enhanced surface coverage of Ni II /Ni III redox center, better dispersion of Ni nuclei, and a low‐Tafel slope. Abstract : With a large pinch of chromium : The enhanced urea oxidation activity of Ni60 Cr40 /C compared to that of Ni/C is attributed to its improved charge‐transfer kinetics, better dispersion of Ni nuclei, high surface coverage of Ni II /Ni III redox center, and a low Tafel slope.